Influence of educational program directed at patients with prehypertension and hypertension on pressure values, biochemical variables, arterial stiffness and expression of metalloproteinases 2 and 9 (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Considering that chronic disease treatment is seen as a challenge to health professionals, the adherence to therapy has been studied in several variables, such as socio-economic aspects, medicines, habits of daily life and food. The aim of the proposed study is to evaluate the influence of an educational program directed at patients with prehypertension and hypertension on pressure levels, biochemical variables, arterial stiffness and matrix metalloproteinase 9 (MMP-9). It is a case-control study. The participants will be allocated to three groups: 50 individuals with normal blood pressure;  80 with prehypertension; and 80 patients with hypertension in outpatient follow up with controlled blood pressure levels. Socio-demographic and behavioral data will be collected through interviews. Blood will be collected for biochemical analysis and the determination of MMP levels. Arterial stiffness will be evaluated through ambulatory blood pressure monitoring. The level of significance will be set to 5% (p